Applying Green Marketing Strategies In Economic Institutions To Achieve Sustainable Performance In Response To Their External Environment - Aouina, Fatima (Journal of Ecohumanism, 2025)
This study aims to identify the strategies adopted by institutions in response to their external environment in order to achieve sustainable performance. This is done by examining the extent to which institutions rely on adopting green marketing strategies based on their external environment to ultimately achieve sustainable performance. To achieve the objectives of the study, a sample of Algerian institutions was selected and surveyed using a questionnaire specifically designed for this purpose. The results indicate that Algerian institutions adopt a defensive strategy to achieve their economic performance, while they adopt an aggressive strategy to achieve their environmental and social performance, thereby attaining sustainable performance.